RECQ1 expression is upregulated in response to DNA damage and in a p53-dependent manner - Parvathaneni, Swetha; Lu, Xing; Choudhary, Ritu; Lal, Ashish; Madhusudan, Srinivasan; Sharma, Sudha (Impact Journals, 2017)
Sensitivity of cancer cells to DNA damaging chemotherapeutics is determined by DNA repair processes. Consequently, cancer cells may upregulate the expression of certain DNA repair genes as a mechanism to promote chemoresistance. Here, we report that RECQ1, a breast cancer susceptibility gene that encodes the most abundant RecQ helicase in humans, is a p53-regulated gene, potentially acting as a defense against DNA damaging agents. We show that RECQ1 mRNA and protein levels are upregulated upon treatment of cancer cells with a variety of DNA damaging agents including the DNA-alkylating agent methylmethanesulfonate (MMS). The MMS-induced upregulation of RECQ1 expression is p53-dependent as it was observed in p53-proficient but not in isogenic p53-deficient cells. The RECQ1 promoter is bound by endogenous p53 and is responsive to p53 in luciferase reporter assays suggesting that RECQ1 is a direct target of p53. Treatment with the chemotherapeutic drugs temozolomide and fotemustine also increased RECQ1 mRNA levels whereas depletion of RECQ1 enhanced cellular sensitivity to these agents. These results identify a previously unrecognized p53-mediated upregulation of RECQ1 expression in response to DNA damage and implicate RECQ1 in the repair of DNA lesions including those induced by alkylating and other chemotherapeutic agents.